Prior vaccination promotes early activation of memory T cells and enhances immune responses during SARS-CoV-2 breakthrough infection - Painter, Mark M.; Johnston, Timothy S.; Lundgreen, Kendall A.; Santos, Jefferson J. S.; Qin, Juliana S.; Goel, Rishi R.; Apostolidis, Sokratis A.; Mathew, Divij; Fulmer, Bria; Williams, Justine C.; McKeague, Michelle L.; Pattekar, Ajinkya; et al. (Nature immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection of vaccinated individuals is increasingly common but rarely results in severe disease, likely due to the enhanced potency and accelerated kinetics of memory immune responses. However, there have been few opportunities to rigorously study early recall responses during human viral infection. To better understand human immune memory and identify potential mediators of lasting vaccine efficacy, we used high-dimensional flow cytometry and SARS-CoV-2 antigen probes to examine immune responses in longitudinal samples from vaccinated individuals infected during the Omicron wave. These studies revealed heightened spike-specific responses during infection of vaccinated compared to unvaccinated individuals. Spike-specific cluster of differentiation (CD)4 T cells and plasmablasts expanded and CD8 T cells were robustly activated during the first week. In contrast, memory B cell activation, neutralizing antibody production and primary responses to nonspike antigens occurred during the second week. Collectively, these data demonstrate the functionality of vaccine-primed immune memory and highlight memory T cells as rapid responders during SARS-CoV-2 infection. Wherry and colleagues define the kinetics of vaccine-primed recall immune responses during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) breakthrough infection, highlighting rapid activation of memory T cells and broadly enhanced immune responses in previously vaccinated individuals.